Healthy lifestyle boosts memory and lowers the risk of Alzheimer's disease / Dr. Hanish Singh Jayasingh Chellammal, Dr. Gurmeet Kaur Surindar Singh and Prof. Dato' Dr. Abu Bakar Abdul Majeed - Jayasingh Chellammal, Hanish Singh; Surindar Singh, Gurmeet Kaur; Abdul Majeed, Abu Bakar (Faculty of Pharmacy, 2023)
This article is expressed in conjunction with World Alzheimer's Day (21st September) and is a pivotal prospect to know the importance of lifestyle factors and food habits for improving memory and enhancing neuroprotection. An estimated 55 million people globally are living with dementia, which will rise to over 150 million by 2050 in tandem with the increasing ageing population. A steep escalation in Alzheimer's cases is witnessed in South Asian and Western Pacific nations' ageing populations. In Malaysia's elderly population, 8.6% have dementia and according to Alzheimer's Disease International, 123,000 people had dementia in 2015. It is a great concern to understand that this figure will rise to 261,000 by 2030 and reach 590,000 by 2050. The accuracy of this statistic may be compromised due to insufficient awareness and acceptance of dementia as a natural component of the ageing process, resulting in cases that remain undiagnosed and untreated.